Implementation of Halal and Haram Concepts in E-Commerce Transactions: A Review of Sharia Economic - Tedy Tedy; Ahdiyatul Hidayah (Saqifah: Jurnal Hukum Ekonomi Syariah, 2024)
Advances in digital technology have changed the way people make transactions, including through e-commerce platforms that are increasingly popular. For Muslims, compliance with sharia principles, especially related to the concepts of halal and haram, is becoming increasingly important. This article discusses the application of halal and haram concepts in e-commerce transactions from the perspective of sharia economic law. Through a qualitative approach and literature review method, this study explores important aspects that need to be considered so that e-commerce transactions are in accordance with sharia law. The main findings show that to comply with sharia, products and services offered through e-commerce must meet halal standards, including not containing prohibited materials and not engaging in prohibited activities such as riba and maysir. In addition, transparency in the transaction process is important to avoid the element of gharar (uncertainty). This research also emphasizes the importance of protecting consumer rights and fairness in transactions. By ensuring the implementation of halal and haram concepts, e-commerce transactions can provide economic benefits while being in line with Islamic teachings, supporting the creation of ethical and sustainable trade.